Quantum Computing and AI: Impacts & Possibilities - Bhupesh Rawat; Nidhi Mehra; Ankur Singh Bist; Muhamad Yusup; Yulia Putri Ayu Sanjaya (ADI Journal on Recent Innovation, 2022)
Quantum computing is one of the emerging technologies. Different communities and research organizations are working to bring quantum computing applications into reality. Artificial Intelligence is another emerging area and getting stable with time. This paper, the main objective is to find out the impact of quantum computing research growth for AI applications. Thus, the method used in this study uses computational methods. so that this research can be concluded regarding the growing impact of quantum computing research for a given AI application. This paper also presents the impact and possibilities of quantum computing in the field of artificial intelligence.